2020
DOI: 10.4274/jpr.galenos.2019.88942
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mother’s Lullaby on Preterm Infants’ Physiological Parameters

Abstract: Inappropriate auditory stimulants lead to neonatal stress and changes in physiological parameters. Nowadays, particular emphasis is placed on the developmental aspects of the care of preterm infants. The lullaby is a suitable auditory stimulus for preterm infants, which as a subtype of developmental care decreases stress responses. This study investigates the effects of lullabies in the mothers' own voices on preterm infants' physiological parameters. Materials and Methods:This single group study is a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Previous research has already evidenced that these interventions have a beneficial effect on PTI's brain development, mainly in the improvement of emotional regulation capabilities 14 . However, in the current review, conflicting results were found for outcomes such as HR, RR, satO2, BP, weight gain, circadian rhythm, feeding behaviour or rate and behavioural states 29,32‐34,37,39,40,46,49,51‐55 …”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Previous research has already evidenced that these interventions have a beneficial effect on PTI's brain development, mainly in the improvement of emotional regulation capabilities 14 . However, in the current review, conflicting results were found for outcomes such as HR, RR, satO2, BP, weight gain, circadian rhythm, feeding behaviour or rate and behavioural states 29,32‐34,37,39,40,46,49,51‐55 …”
Section: Discussionmentioning
confidence: 60%
“…Discrepancies were resolved by discussion and consensus. The overall results showed that 27 RCTs had a low (69.2%), 17‐43 7 had a moderate (17.9%) 44‐50 and 5 had a high (12.8%) risk of bias 51‐55 …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations